Targeting the hypnozoite reservoir of Plasmodium vivax: the hidden obstacle to malaria elimination. - Wells, T; Burrows, J; Baird, J (2010)
Plasmodium vivax is the major species of malaria parasite outside Africa. It is especially problematic in that the infection can relapse in the absence of mosquitoes by activation of dormant hypnozoites in the liver. Medicines that target the erythrocytic stages of Plasmodium falciparum are also active against P. vivax, except where these have been compromised by resistance. However, the only clinical therapy against relapse of vivax malaria is the 8-aminoquinoline, primaquine. This molecule has the drawback of causing haemolysis in genetically sensitive patients and requires 14 days of treatment. New, safer and more-easily administered drugs are urgently needed, and this is a crucial gap in the broader malaria-elimination agenda. New developments in cell biology are starting to open ways to the next generation of drugs against hypnozoites. This search is urgent, given the time needed to develop a new medication.